The base of the ribosomal P stalk from Methanococcus jannaschii: crystallization and preliminary X‐ray studies. Issue 11 (1st November 2013) - Mitroshin, Ivan; Gabdulkhakov, Azat; Garber, Maria
Abstract : The lateral P stalk in archaeal/eukaryotic ribosomes and the L12 stalk in bacterial ribosomes play a pivotal role in specific binding to the ribosome and recruiting translational factors during protein biosynthesis. The P stalk consists of the ribosomal proteins L11, P0 and P1. The proteins P0 and P1 form the complex that binds 23S rRNA through the N‐terminal domain of the P0 protein. Ribosomal protein L11 binds to the same region of 23S rRNA and together with the protein P0 forms the base of the stalk. The structure of the ribosomal protein L11 from archaea has been solved, but with several missing segments. Here, the preparation and crystallization of a ternary complex consisting of the ribosomal protein L11, the two‐domain N‐terminal fragment of the ribosomal protein P0 and a specific fragment of 23S rRNA from the archaeon Methanococcus jannaschii are reported. The crystals belonged to the monoclinic space group P 21, with unit‐cell parameters a = 72.4, b = 88.5, c = 95.2 Å, β = 102.2°. A complete diffraction data set has been collected to a resolution of 2.9 Å using an in‐house rotating‐anode X‐ray generator.